Evaluation of single and three way hybrids of sunflower (Helianthus annuus L.) for Alternaria leaf blight: EVALUATION OF SUNFLOWER FOR ALTERNARIA LEAF BLIGHT - S NEELIMA; K G PARAMESHWARAPPA (Journal of Oilseeds Research, 2013)
A field experiment was conducted at Dharwad, Karnataka, India during the rainy season of 2006 to record the degree of incidence of Alternaria leaf blight in single and three way hybrids of sunflower (Helianthus annuus L.) under natural epiphytotic conditions at days to 50 % flowering and physiological maturity. The parental lines CMS 17 A, CMS 103 A, DCMS 51 A and R 64 were moderately resistant to leaf blight. The resistant reaction in two single (CMS 17 A x RHA 6D-1 and CMS 17 A x RHA 271) crosses was noticed when atleast one of the parents in the cross combination had moderate resistant reaction. Three way crosses even after diversification with inbred lines concerned has not yielded resistance over corresponding single cross hybrids. However, inclusion of inbreds DSI 2 and DSI 1017 which were moderately resistant as third parent in hybrid combinations of 103 A x DSI 2 x R 64 and DCMS 51 A x DSI 1017 x RHA 6D-1 ended up with resistance reaction with 2 and 4 grade, respectively. Hence, diversification may either improve or reduces resistance levels of three way crosses indicating that caution is to be exercised in selecting the parents for hybridization as well as the second parent for diversification.